ANALISIS YURIDIS NORMATIF PERAN KORPS BRIMOB POLRI DALAM PENANGANAN KONFLIK PELANGGARAN HUKUM DI PAPUA OLEH KELOMPOK KRIMINAL BERSENJATA - Dandel, Lukman Syafri; Maryano, Maryano; Kristiawanto, Kristiawanto (Gapenas Publisher, 2025)
This study analyzes the role of the Indonesian National Police Mobile Brigade Corps (Brimob) in handling conflicts of law violations in Papua by the Armed Criminal Group (KKB), which has been categorized as a terrorist group. Using a normative legal research approach, this study examines the legal basis, implementation, and challenges faced by Brimob in security operations in Papua based on Law Number 2 of 2002 concerning the Indonesian National Police and other relevant regulations. The results show that Brimob has a strategic role as the National Police's striking force in handling high-intensity conflicts in Papua, through preventive, repressive, and recovery approaches. Legal protection for Brimob members in carrying out these tasks is regulated in legislation, but its implementation still has challenges. This study concludes that there is needs to increase capacity and operational support for Brimob and strengthen inter-agency coordination to improve the effectiveness of conflict management in Papua.